Pooled screening for CAR function identifies novel IL-13Rα2-targeted CARs for treatment of glioblastoma - Douglas A Lauffenburger; Khloe S Gordon; Caleb R Perez; Andrea Garmilla; Maxine S Y Lam; Joey J Y Aw; Anisha Datta; Andrea Pavesi; Michael E Birnbaum (Journal for ImmunoTherapy of Cancer)
Background Chimeric antigen receptor (CAR) therapies have demonstrated potent efficacy in treating B-cell malignancies, but have yet to meaningfully translate to solid tumors. Nonetheless, they are of particular interest for the treatment of glioblastoma, which is an aggressive form of brain cancer with few effective therapeutic options, due to their ability to cross the highly selective blood-brain barrier.Methods Here, we use our pooled screening platform, CARPOOL, to expedite the discovery of CARs with antitumor functions necessary for solid tumor efficacy. We performed selections in primary human T cells expressing a library of 1.3×106 third generation CARs targeting IL-13Rα2, a cancer testis antigen commonly expressed in glioblastoma. Selections were performed for cytotoxicity, proliferation, memory formation, and persistence on repeated antigen challenge.Results Each enriched CAR robustly produced the phenotype for which it was selected, and one enriched CAR triggered potent cytotoxicity and long-term proliferation on in vitro tumor rechallenge. It also showed significantly improved persistence and comparable tumor control in a microphysiological human in vitro model and a xenograft model of human glioblastoma, but also demonstrated increased off-target recognition of IL-13Rα1.Conclusion Taken together, this work demonstrates the utility of extending CARPOOL to diseases beyond hematological malignancies and represents the largest exploration of signaling combinations in human primary cells to date.